2007
DOI: 10.1057/palgrave.abm.9200208
|View full text |Cite
|
Sign up to set email alerts
|

Integration Management of Western Acquisitions in Japan

Abstract: In recent years, Japan has seen a sharp increase in foreign cross-border merger and acquisition (M&A) transactions. Among the larger cross-border M&A transactions in Japan, a few multinational companies are already struggling with their acquisitions. In this study, we systematically analyzed and compared the unsuccessful DaimlerChrysler-Mitsubishi acquisition with the successful RenaultNissan acquisition. We collected secondary data and conducted interviews with both Japanese and foreign managers. Despite some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…; Ellis et al . ; Froese and Goeritz ; Piske ; Schweiger and DeNisi ; Searle and Ball ). Distributional justice refers to equality between the involved firms, but is a double‐edged sword.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Ellis et al . ; Froese and Goeritz ; Piske ; Schweiger and DeNisi ; Searle and Ball ). Distributional justice refers to equality between the involved firms, but is a double‐edged sword.…”
Section: Resultsmentioning
confidence: 99%
“…While research has found that differences in national culture can affect the integration positively as well as negatively, differences between the organizational cultures are often harmful (Cheng and Seeger ; Froese and Goeritz ; Pepper and Larson ; Vaara ; Vaara et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Born-global firms from Japan would be less constrained by the Japanese context, and thus their IHRM could be quite different from that of traditional Japanese MNCs. As for cross-border M&A, we know little about what happens in IHRM if a Japanese firm is acquired by a foreign MNC (Froese and Goeritz, 2007), or if Japanese MNCs acquire and integrate foreign firms.…”
Section: Internationalization Of Hrm From Strategic Perspectivesmentioning
confidence: 99%
“…In addition, as Renault successfully integrated Nissan in Japan (see Froese & Goeritz, 2007) and shortly thereafter Samsung in Korea, it will show why Renault has been successful in integrating target companies. Finally, it will compare cross-border acquisitions in Japan with those in Korea.…”
mentioning
confidence: 96%